2010
DOI: 10.1016/j.actamat.2009.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic processes of domain switching in lead zirconate titanate under cyclic mechanical loading by in situ neutron diffraction

Abstract: The performance of ferroelectric ceramics is governed by the ability of domains to switch. A decrease in the switching ability can lead to degradation of the materials and failure of ferroelectric devices. In this work the dynamic properties of domain reorientation are studied. In situ time-of-flight neutron diffraction is used to probe the evolution of ferroelastic domain texture under mechanical cyclic loading in bulk lead zirconate titanate ceramics. The high sensitivity of neutron diffraction to lattice st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Using Diffraction (MAUD) package. A total of 147 recorded data sets were analyzed utilizing a script-based approach in combination with either SMARTSware [36] code which utilizes the General Structure Analysis System (GSAS) to perform a single peak fit or gsaslanguage to refine the entire spectrum. The latter custom sequential script models up to four phases simultaneously, namely 2H graphite, 3R graphite, UO2 and UxC with the site occupancy x ranging between 0.5 and 1, describing UC2 and UC respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Using Diffraction (MAUD) package. A total of 147 recorded data sets were analyzed utilizing a script-based approach in combination with either SMARTSware [36] code which utilizes the General Structure Analysis System (GSAS) to perform a single peak fit or gsaslanguage to refine the entire spectrum. The latter custom sequential script models up to four phases simultaneously, namely 2H graphite, 3R graphite, UO2 and UxC with the site occupancy x ranging between 0.5 and 1, describing UC2 and UC respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, a higher loading rate results in a smaller dissipated energy, compared to that of a larger stress. is is because P51 ceramics are time-dependent materials [16][17][18][19], and strain would become larger under stress being held or even a constant. A lower loading rate denotes a longer duration on the specimen, which results in a larger energy at the same stress amplitude.…”
Section: Effects Of Stress Amplitude and Loading Rate On Energymentioning
confidence: 99%
“…Webber et al [18] indicated that the nonlinear strain can be attributed to the domain wall motion and accompanying misfit strains surrounding switching domain. Furthermore, Pojprapai et al [19] theoretically proposed a rheological model representing time-dependent deformation and separated the steady-state creep strain from transient creep strain macroscopically under the square wave cyclic loading.…”
Section: Introductionmentioning
confidence: 99%
“…In its applications such as nonvolatile ferroelectric memories and multilayer actuators, fatigue that occurs under repetitive application of electromechanical loads has been nominated as the major hindrance to extending the potential of this material . Ferroelectric devices using PZT are usually operated under electrical and/or mechanical cyclic loading, leading to degradation of the performance . The bipolar electrical fatigue behaviors are usually exhibited as the decrease in polarization as well as increase in the coercive field.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Ferroelectric devices using PZT are usually operated under electrical and/or mechanical cyclic loading, leading to degradation of the performance. [6][7][8][9][10] The bipolar electrical fatigue behaviors are usually exhibited as the decrease in polarization as well as increase in the coercive field.…”
Section: Introductionmentioning
confidence: 99%